Estrutura de equipes-cliente em projeto de implantação de sistemas de informação no setor público: evidências em reuniões por videoconferência entre organizações federais. - Correia, Rony Rodrigues (2013)
The concept of structure is a complex one that involves many variables. The socio-technical approach allows putting in practice the application of this concept in the area of information systems. Specifically, on customer teams of information systems deployment projects, the structure is part of a performance evaluation model. This study aimed to identify discussions about the socio-technical structure of customer teams in videoconferences conducted between customer teams and development team, in the process of deploying information systems in public sector. Initially, it was performed a compilation of theoretical elements which form the customer team structure. Afterwards, it was examined the occurrence and the characterization of discussions for each element. It was observed that the elements Formality & Knowledge Sharing and Cooperativeness have theoretical and empirical relations. The element Contextual Adaptattion/Integration was not registered in empirical research, being this the result of the activity nature of the public sector. Finally, it was proposed the model CUTEST (Customer Teams Socio-technical Structure) for defining the structure and entry for performance evaluation models of customer teams of information systems deployment projects in the public sector.